The fringes of belief : English literature, ancient heresy, and the politics of freethinking, 1660-1760 - Ellenzweig, Sarah (Stanford University Press, 2008)
A literary study of freethinking and religious skepticism in the English Enlightenment. Ellenzweig argues that a literature of English freethinking has been overlooked because it unexpectedly supported aspects of institutional religion. She analyzes works by, among others, John Wilmot, Aphra Behn, Swift and Pope.